ICE PHENOMENA IN THE WARTA RIVER IN POZNAŃ IN 1961– 2010 - Kornaś, Marika (Quaestiones Geographicae, 2014)
The article presents variability of ice phenomena in the Warta River in Poznań based on data recorded in the water gauge station in Poznań - Roch Bridge in 1961-2010. The work aims to characterize and analyze ice phenomena and related hazards. First dates (freeze date), last dates (thaw date) and duration of ice phenomena and particular forms of ice, i.e. frazil ice, border ice, ice cover, ice floes and ice jam, were determined. In case of ice cover, its thickness was also analyzed. In the analyzed period, ice phenomena in the Warta River in Poznań had the maximum duration of 118 days, the earliest date appearance was on November 7 and the last on March 28. The first ice form to appear was frazil ice, the last ice floes and the longest lasting - ice floes. In the entire analyzed period, 15 winter seasons featured ice cover. The longest duration of ice cover was 29 days and its maximum thickness was 8 cm.